Buoyancy driven convection in micropolar fluid with controller and variable boundaries - Mohd Mokhtar, Nor Fadzillah; Khalid, Izzati Khalidah; Md. Arifin, Norihan (WSEAS Press, 2015)
The effect of controller (feedback control) is applied to the steady Rayleigh-Benard convection in a horizontal micropolar fluid layer. The bounding surfaces of the liquids are considered to be free-free, rigid-free, and rigid-rigid with combination isothermal on the spin-vanishing boundaries. A linear stability analysis is used and the Galerkin method is employed to find the critical stability parameters numerically. It is shown that the critical Rayleigh number increases as the value of feedback control increases.